Public Sector Audit Effectiveness in Malaysia: A Mixed Method Pilot Study - Mohd Noor, Nor Raihana Asmar; Mohd Noor, Nor Raihana Asmar; Mansor, Noorhayati (International Journal of Psychosocial Rehabilitation, 2020)
Issues surrounding internal audit effectiveness are still lacking in the current literature especially on the government sector internal audit. Thus, a mixed method pilot test was conducted to assess the effects of four determinants of the effectiveness of internal audit in the public sector. They include (i) internal audit quality; (ii) proficiency of internal auditors; (iii) independence; and (iv) types of audit. In addition, this study proposes the practice of whistleblowing as a mediating variable in the relationships between the four determinants. A total of 30 final responses were received from internal auditors from public universities for this pilot study survey and an interview with a head of internal auditor was conducted to validate the data. The internal auditors involved in the pilot study exhibited positive and constructive responses hence it confirmed the reliability of the determinants. The impacts from the practice of whistleblowing will provide further evidence to strengthen the internal control system and practices in improving the accountability and transparency of the public sector. This paper further supplements previous literatures on internal audit effectiveness by imploring its nature and determinants in the public sector agencies. This paper pioneers the study that focuses on the relationship of the practices of whistleblowing and public sector effectiveness.